Risk factor assessment and screening for diabetes in field practice area of a private medical college in Thiruvallur district of Tamil Nadu - Dev, Sathish; Jain, Timsi; P., Sivaprakasam; Raja, Dinesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes, which was known to be an epidemic in the urban areas, has been found to be increasing rapidly in the rural areas too as a result of the socioeconomic transitions. Diabetes is no longer only a disease of the elderly but is one of the major causes of morbidity and mortality affecting youth and middle aged people. Methods: Screening camp for diabetes was conducted by the Department of Community Medicine in three different areas in the field practice area of Saveetha Medical College and Hospital viz. Thirumazhisai, Kuthambakkam and Velavedu in Thiruvallur district of Tamil Nadu on 7th April 2016 as a part of World Health Day 2016 celebration. Data was collected using a predesigned interview schedule. Descriptive statistics was calculated using rates, ratios & proportions. Univariate analysis was done using Chi square test to find the association between various factors and diabetes status. A parsimonious regression model was developed to find the predictor variables for diabetes. Results: A total of 188 people aged above 18 years attended the screening camps. Majority of the camp attendees were females (62.2%). Proportion of people having diabetes (already diagnosed plus newly screened) was found to be 18.1% out of which 3.2% were screened positive for diabetes. On regression analysis, Intake of alcohol and perceived stress were found to be significantly associated with diabetes (p<0.05). Conclusions: This study highlights a significant burden of undiagnosed cases of diabetes in the community. This indicates the need for systematic screening and awareness programs to identify the undiagnosed cases in the community and offer early life style modifications, treatment and regular follow up to such individuals.